2001
DOI: 10.1002/1521-396x(200108)186:2<309::aid-pssa309>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Optical Properties of CVD Diamond at Elevated Temperatures

Abstract: The combination of low absorption and extreme mechanical and thermal properties make diamond a compelling choice for some more extreme far infrared (8-14 mm) window applications. The optical properties of CVD diamond at elevated temperatures are critical to many of these extreme applications. The absorption coefficient of diamond has been assessed on polished diamond samples with a variety of optical characteristics by heating samples up to 550 C and measuring transmission in a grating IR spectrophotometer. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…The introduction of Laser Flash technique has been depicted in details anywhere [10]. The pulse length of Xenon Flash lamp and Nd:YAG laser used in LFA447 and LFA457 was 0.06 ms and 0.33 ms respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of Laser Flash technique has been depicted in details anywhere [10]. The pulse length of Xenon Flash lamp and Nd:YAG laser used in LFA447 and LFA457 was 0.06 ms and 0.33 ms respectively.…”
Section: Methodsmentioning
confidence: 99%
“…CVD diamond films exhibit some anisotropy in thermal conductivity due to their column growth [8], and in same cases they must be exposed to extreme operating temperatures when used in devices [6,9,10]. Various methods have been utilized to determine the temperature-dependent thermal properties of CVD diamond, such as laser flash technique [11], transient thermal grating technique [12], and steady-state heater bar method [13,14], et al, in which laser flash technique is a common and reliable method for through-thickness thermal conductivity diamond over a wide temperature range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though literature on spectroscopic properties of diamond is immense, experimental data about its emissivity is scarce. Emission spectra of macroscopic diamonds in relatively narrow wavelength range relevant for diamond applications as optical windows for CO 2 lasers were reported by Mollart and Lewis (2001). It was shown that the emissivity (ε) spectra closely follow the expected behaviour 1-R, where R is the reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…They analysed their data using a model that has the inconsistency that the absorption derives from transitions associated with the creation of single phonons, which are forbidden in diamond [2][3][4][5]. Recently, Mollart and Lewis [6] published, without interpretation, experimental data of a careful study of the temperature dependence of the spectrum between 500 and 5000 cm À1 , and Meykens et al [7] have used a combination of laser calorimetry and photo-thermal deflection spectroscopy to measure the absorption of natural diamond at 10.6 mm for 300 K < T < 800 K. In this paper we present absorption data at the CO 2 laser wavelength of 10.6 mm for the temperature range of 300 to 650 K, taken on high-purity chemical vapor deposited (CVD) diamond. The absorption is shown to be caused by several processes, each of which may be calculated explicitly.…”
mentioning
confidence: 99%